Georreferenciación y su aporte en la lectura de medidores para los usuarios del Cantón Montalvo - Sumba Guamán, Nury Johanna (2019)
Electric power is a very important service nowadays for people, because without it the digital world would not be possible. Therefore, this must be a quality service from the process in which it reaches the homes until its correct billing. The reading system of electrical meters of the users of the canton Montalvo, has drawbacks in the exact location of these meters, causing problems when taking the reading on the meters, due to the geographical ignorance of each of them. Outside of Montalvo canton, there are a large number of users that consume this service, but being a very large extension, many lords responsible for taking measures are lost or do not reach the indicated place, so in Consequently, they invoice values ​​that do not belong to that meter, because they must Cover a route and it can not be empty. So this causes great discomfort to the users due to the fact that payrolls with unreal values ​​are issued Currently, there is no system to read the measures of the consumption of the meters, simply those in charge of doing it, use their device mobile phone to take pictures of each meter and then record the consumption determined owner of it. The present case study arises from the need to identify and analyze the requirements for the development of a mobile georeferencing application for the software for reading electric meters for users of the Montalvo canton.